2000
DOI: 10.1089/thy.2000.10.19
|View full text |Cite
|
Sign up to set email alerts
|

N-ras Mutation in Poorly Differentiated Thyroid Carcinomas: Correlation with Bone Metastases and Inverse Correlation to Thyroglobulin Expression

Abstract: Codon 61 of the N-ras oncogene was screened for mutations in 99 surgically resected thyroid carcinomas by a polymerase chain resection (PCR)-based method (PCR-primer introduced restriction with enrichment of mutant alleles [PCR-PIREMA]). A point mutation of the N-ras oncogene at the codon 61 was detected in 16 of 99 (16.2%) thyroid carcinomas examined by this method. No RAS alteration was detected in the group of 11 medullary thyroid carcinomas, while 3 of 31 (10.0%) papillary carcinomas, 2 of 5 (40%) follicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
1
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(93 citation statements)
references
References 16 publications
4
77
1
11
Order By: Relevance
“…Studies on RAS mutation in different types of thyroid cancer have shown that these mutations are observed in both malignant and benign types of tumors [97]. However, codon 61 point mutations have been especially reported to cause tumor progression in an aggressive manner [98,99].…”
Section: Rasmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on RAS mutation in different types of thyroid cancer have shown that these mutations are observed in both malignant and benign types of tumors [97]. However, codon 61 point mutations have been especially reported to cause tumor progression in an aggressive manner [98,99].…”
Section: Rasmentioning
confidence: 99%
“…In PTCs, RAS mutations are found at relatively low frequencies, in approximately 10% of tumors. In follicular thyroid carcinomas, 40-50% of tumors carry RAS mutations [87,91,96], which may correlate with poor prognosis and tumor dedifferentiation [97,240]. RAS mutations may influence tumor dedifferentiation, as they are found with high frequency in ATCs.…”
Section: Targeting Rasmentioning
confidence: 99%
“…RAS mutation, although most significant in the diagnosis of follicular thyroid cancer (FTC), is also reported in papillary thyroid cancer (PTC) and ATC [35,36]. From studies of different histological types of thyroid cancer, up to 60% of ATC was found to harbor RAS mutation [36][37][38]. In a stepwise process, RAS appeared to be an "early-stage" mutation.…”
Section: Ret/ptc-ras-rafmentioning
confidence: 99%
“…Several molecular alterations have been investigated to define PDTC histogenesis, but the molecular genetic data so far reported in the literature reflect the heterogeneity of the case series analyzed, as the result of the discrepancies in PDTC diagnosis and classification. Generally, irrespective of the selection criteria applied, RAS point mutations appear to be a common molecular alteration in these tumors, although they were found with highly variable frequency and wide variation in specific types of RAS mutations [4,28,29]. Likewise, BRAF mutations were detected in poorly differentiated carcinomas having residual papillary carcinoma foci [30, 31], but not in cases lacking the morphologic evidence of transition from well differentiated papillary to poorly differentiated carcinoma [32].…”
Section: ) Mitoses and Necrosis Vs Growth Patternmentioning
confidence: 99%